2010
DOI: 10.3109/03639045.2010.489561
|View full text |Cite
|
Sign up to set email alerts
|

Low powder mass filling of dry powder inhalation formulations

Abstract: Initial studies suggest that the OMNIDOSE((®)) technology is readily adaptable for the dosing of low masses of DPI excipients and formulations and demonstrate the value of thoroughly evaluating powder performance at laboratory scale prior to pilot scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Each API must be evaluated itself for feasibility, and we have not yet scaled micronized TIG to these instruments. Typically, low fill weights exacerbate difficulty in achieving capsule target weight uniformity; however, in the case of high dose powders some of this concern is reduced. In addition, the observed lack of flow rate-dependent changes and efficient dispersion of micronized TIG at lower pressures indicates lack of cohesivity, which is likely to translate to good powder handling as well as makes it a promising drug to be administered via inhalation, which is robust to changes in patient characteristics. Future studies will evaluate scaling powder filling to capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Each API must be evaluated itself for feasibility, and we have not yet scaled micronized TIG to these instruments. Typically, low fill weights exacerbate difficulty in achieving capsule target weight uniformity; however, in the case of high dose powders some of this concern is reduced. In addition, the observed lack of flow rate-dependent changes and efficient dispersion of micronized TIG at lower pressures indicates lack of cohesivity, which is likely to translate to good powder handling as well as makes it a promising drug to be administered via inhalation, which is robust to changes in patient characteristics. Future studies will evaluate scaling powder filling to capsules.…”
Section: Discussionmentioning
confidence: 99%
“…developed a process from lab scale to pilot scale for low-mass filling using the OMNIDOSE filling technology. The experience gained from this study suggested that the filling performance on lab-scale instruments can provide useful information for formulation development and scale-up Figure provides a schematic for both dosator and vacuum drum fillers.…”
Section: Overview For Modeling Inhalable Dry Powder Filling Processesmentioning
confidence: 99%
“…The experience gained from this study suggested that the filling performance on lab-scale instruments can provide useful information for formulation development and scale-up. 99 Figure 7 provides a schematic for both dosator and vacuum drum fillers. Tamp filling systems, unlike dosator systems, are automated filling devices that require less formulation compaction and are ideal for loading highly potent drugs.…”
Section: Introduction To the Filling Instrumentsmentioning
confidence: 99%
“…However, lowdose filling leads to challenges during manufacturing. Modern capsule-filling technologies [173][174][175] take into account these challenges and apply special adjustment to the machines for accurate dosing. For example, high-end continuous dosator machines like the Planeta 100 ( Fig.…”
Section: Low-dose Fillingmentioning
confidence: 99%